Perforated dried blood spots: a novel format for accurate microsampling. (October 2011) - Li, Fumin; Zulkoski, John; Fast, Douglas; Michael, Steve
Dried blood spots (DBS) in their current format encounter challenges in bioanalysis using fixed areas, including but not limited to, waste of DBS samples (only a fraction is used for analysis), the need for sample punching leading to concerns of sample carryover, uncertainty for accurate recovery assessments and hematocrit (HCT) effects. Here we describe a novel concept, namely perforated dried blood spots (PDBS), for accurate microsampling that addresses previous challenges. PDBS discs were prepared from regular filter paper, with a diameter of 6.35 mm and a thickness of 0.83 mm. An accurate amount of blood sample (5–10 µl), was deposited, dried and stored on the PDBS discs. Upon sample analysis, PDBS samples are simply pushed by single-use pipette tips into 96-well plates. The proof-of-concept study was carried out on a PDBS LC–MS/MS assay development and validation under GLP criteria for the quantitation of lansoprazole in human whole-blood (K3 EDTA). Particularly, the effect of HCT on the accuracy of quantitation was found to be related to recovery from PDBS samples. In all, PDBS was proved to be a viable alternative to conventional DBS, offering additional advantages of complete sample utilization, no requirement for punching, ease of recovery assessments, and elimination of sampling influence due to HCT levels.